English Kids’ Songs: Effective Media for Teaching Vocabulary - Rochma, Annisa; Mukminatus Zuhriyah (LPPM Universitas Hasyim Asy'ari Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research aims to find out the effectiveness of using English kids' songs to teach vocabulary. It was conducted in a private elementary school located in Jombang area in the academic year of 2023-2024. The population of this research was the fourth-grade students, consisting of three classes with a total of 62 students. The sample, selected using purposive sampling, included 18 students of class IV B. This study used a pre-experimental design with pre-tests and post-tests to measure students' vocabulary improvement before and after learning using English kids' songs. The pre-test checked their initial vocabulary while the post-test measured their progress. The results were analyzed by descriptive statistics and a-paired sample t-test. The results showed that vocabulary before being treatment was still